1994
DOI: 10.1007/bf00173046
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m methoxyisobutylisonitrile localizes an ectopic ACTH-producing tumour: case report and review of the literature

Abstract: Extensive investigation including whole-body examinations with computed tomography and magnetic resonance imaging did not detect the suspected ectopic ACTH-producing tumour in a patient with advanced Cushing's syndrome and hypokalemic alkalosis. Gamma camera examination with technetium-99m methoxyisobutylisonitrile (MIBI) depicted the tumour, which was localized in the anterior neck and mediastinum. This was later verified by surgery. 99mTc-MIBI is normally used for myocardial scintigraphy. Its accumulation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…1,2 Although this imaging technique has a high sensitivity for locating hyperfunctioning parathyroid glands, false-positive uptake in various other cervical tumors is also known. [3][4][5][6] Paragangliomas or glomus tumors are most commonly located in the head and neck and stem from parasympathetic ganglia. In up to 10% of patients, these tumors may be diagnosed incidentally during imaging performed for multiple reasons.…”
Section: Figurementioning
confidence: 99%
“…1,2 Although this imaging technique has a high sensitivity for locating hyperfunctioning parathyroid glands, false-positive uptake in various other cervical tumors is also known. [3][4][5][6] Paragangliomas or glomus tumors are most commonly located in the head and neck and stem from parasympathetic ganglia. In up to 10% of patients, these tumors may be diagnosed incidentally during imaging performed for multiple reasons.…”
Section: Figurementioning
confidence: 99%
“…It can be used to localize lesions not seen on other scans 10 ) . The 99m technetium-methoxyisobutylisonitrile (MIBI) scan is also helpful to detect ectopic ACTH-producing tumors undiagnosed with CT and MRI 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, these tumors were undetected on plain chest X-ray for such a long period that they commonly resulted in unnecessary adrenal surgery and eventual tumor dissemination 9 . Theoretically, a nuclear medicine scan is an ideal technique for early detection of this kind of tumor 14 . Jacobsson et al reported a patient with an ectopic ACTH-producing tumor, undetected by wholebody CT and MRI, but localized by a 99mTc-MIBI scan 14 .…”
Section: Discussionmentioning
confidence: 99%